201k views
1 vote
3x+y=14 2x-3y+13 solve by substitution

User Ikutsin
by
5.7k points

2 Answers

5 votes


\left\{\begin{array}{ccc}3x+y=14&\to|-3x\\2x-3y=13\end{array}\right\\\\\left\{\begin{array}{ccc}y=14-3x\\2x-3y=13\end{array}\right\\\\substitute\\\\2x-3(14-3x)=13\\2x-(3)(14)-(3)(-3x)=13\\2x-42+9x=13\\11x-42=13\ \ \ |+42\\11x=55\ \ \ |:11\\x=5\\\\\text{substitute the value of x to the first equation}\\\\y=14-3(5)=14-15=-1\\\\Answer:\ x=5;\ y=-1\to(5;-1)

User John Myles White
by
5.9k points
4 votes

3x+y = 14 (1st)

2x-3y =13 (2nd)

(1st) 3x+y=14 ----> y = -3x + 14

Substitute y = -3x + 14 into (2nd) equation 2x-3y = 13

2x - 3(-3x + 14) = 13

2x + 9x - 42 = 13

11x - 42 = 13

11x = 55

x = 5

substitute x = 5 into (1st) equation

y = -3x + 14

y = -3(5) + 14

y = - 15 + 14

y = -1

Answer

x = 5 and y = -1

User Omri Bernstein
by
5.8k points